English Education Model Based on Web-based Autonomous Learning Platform - Zhidan Li, Jing Li (Forest Chemicals Review, 1970)
This paper takes college students in the computer network environment as the research object. Guided by the relevant principles of College English Curriculum Teaching Requirements, combined with constructivist learning theory and autonomous learning theory, this paper studies several elements of college students’ autonomous learning, such as learning motivation, learning methods, learning plan, learning reflection and so on. With the help of comparative research, questionnaire survey, statistical analysis and other research methods, this paper puts forward corresponding countermeasures for the induction, cultivation and combination of relevant elements of college students’ autonomous learning under the network environment. At the same time, this paper expounds the ways to give full play to the advantages under the network environment, mobilize positive factors and improve teaching efficiency. The results of this study have a certain reference value for the English education model based on web-based autonomous learning platform.